Sonochemical and Mechanochemical Synthesis of Alcohols from Aldehydes and Ketones - Indah Mutiara Putri; Ferlana Debbora Dachi; Dhina Fitriastuti; Muhammad Idham Darussalam Mardjan (Indonesian Journal of Chemistry, 2023)
A green, convenient, and scalable synthesis of alcohols through the reduction of aldehydes and ketones has been developed. The green reduction was conducted using two different methods, namely sonochemistry and mechanochemistry. In the former method, the solution of aldehydes or ketones and sodium borohydride was irradiated under ultrasound irradiation. In the latter technique, the reaction mixture was ground under solvent-free conditions. The reduction reaction was performed at room temperature and completed in only 10 min using both protocols. The results showed that aldehydes and ketones with aromatic, heteroaromatic, and aliphatic motifs were tolerated under the reaction conditions, allowing the formation of the corresponding alcohols with the synthetic yields of 75–98% and 77–95% for grinding and sonication methods, respectively. In addition, the reaction can be carried out on a multigram scale.